Introducing Telerehabilitation in Patients with Multiple Sclerosis with Significant Mobility Disability: Pilot Feasibility Study - In Cheol Jeong; Finkelstein, Joseph (2015 International Conference on Healthcare Informatics, 2015)
Recent studies demonstrated that exercise interventions in significantly disabled patients with multiple sclerosis (PwMS) resulted in endurance and strength improvement and reduction of fatigue and spasticity. However engagement in long-term exercise training is limited in these patients due to multiple barriers including mobility, access to an exercise facility, and cost. It is unclear if PwMS with significant mobility disability are willing and able to engage in home-based telerehabilitation. The goal of this study was to assess level of acceptance and ability of these patients to carry out exercises using the telerehabilitation system without supervision. Ten PwMS with significant mobility disability were instructed how to use the telerehabilitation system and were then asked to use it independently according to predefined set of tasks. Feasibility was assessed by ability of study participants to successfully follow exercise tasks provided by a touch screen tablet. Telerehabilitation acceptance was measured by an attitudinal survey. Participant characteristics were: age=53±11, PDDS=5.3±2.4, years with MS=16±9. Average time required to train the patients to use the telerehabilitation system at home for flexibility and resistance exercises was 11±3 minutes and for active arm/leg biking: 3±1 minutes. All patients were able to successfully complete flexibility and resistance exercises and navigate the interface for arm biking exercise. Heart rate readings were affected by noise in some subjects. Active leg cycling was completed by 50% of patients, another half was unable to use it due to severe lower limb mobility impairment. Passive leg cycling supported by a splinting device was successfully operated by 100%. Overall, high acceptance and usability of the system in PwMS with severe mobility disability was demonstrated. This approach has a potential in supporting a comprehensive exercise delivery model in PwMS with significant mobility disability which will support individualized prescription of tailored endurance, strength, and therapeutic physiotherapy exercises.